PENGARUH RETURN ON ASSET, EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rukman; Hanifah; Mike Mega Rahayu (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to determine the effect of Return On Assets, Earning Per Share and Net Profit Margin on the share price of Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2015-2019 Period. The method used in this research is quantitative. The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Of the 45 pharmaceutical company populations sampled in the study, 9 companies were obtained. The sample withdrawal method is purposive sampling. The data analysis techniques used are classical assumption test, multiple regression analysis, correlation analysis, coefficient of determination, t test, and f test. The statistical test results show that the significance value of the Return On Asset Cost is 0.000 <0.05, this means that H0 is rejected and H1 is accepted. So it can be concluded that Return On Asset partially affects the Stock Price.